(untitled) (Research, Society and Development, 2020)
Objective: To explain about the mourning process vis-à-vis COVID-19. Method: This is a narrative review of the literature on the grieving process in the face of the COVID-19 pandemic. Results: Four guiding axes were presented on the theme, namely: grieving process: understanding the grieving diagnosis; persistent complex grieving disorder; I struggle in the context of COVID-19: support strategies and emotional support in mourning during the COVID-19 pandemic. Conclusion: Mourning is a normative process of adaptations to losses, covering emotions, conditions, physical sensations and behavioral changes, requiring health professionals to pay attention to listening, welcoming and observing clinical and psychological signs of mental suffering.